Impact on Hydrological Alteration due to Climate Change in Seti Watershed - Baral, Kushal; Pandey, Vishnu Prasad; Pradhan, Ananta Man Singh (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.003This study provides streamflow and hydrologic alternation in the climate change context in Seti watershed in Nepal, which will assist planners in better managing streamflow and preparing for climate change. The Soil and Water Assessment Tool (SWAT) model was utilized in this study to simulate the hydrological dynamics of the watershed. The model has been calibrated and validated, with satisfactory performance. Future climate is projected based on the latest set of Shared Socio-economic Pathways (SSP) scenarios from CMIP6 global climate model outputs. The response of streamflow to future climate in three future periods (near, 2025-2050), (mid, 2051-2075), and (far, 2076-2100) is analyzed by comparing to a baseline. Results showed projected decrease of up to 20% during winter in both scenarios, and increase of up to 158% (SP245) and 203% (SSP585) during pre-monsoon, increase of up to 120% (SSP245) and 185% (SSP585) during monsoon, and increase of up to 103% (SSP245) and 144% (SSP585) during post-monsoon seasons.